Perbedaan pH Saliva Sebelum Dan Sesudah Mengunyah Permen Karet Xylitol Pada Pemakai Alat Orthodonti Cekat - Gita Komala Dewi; Susilarti Susilarti; Almujadi Almujadi (Poltekkes Kemenkes Yogyakarta, 2018)
Orthodontic treatment may lead to environmental changes in the oral cavity that may occur in a number of users of the orthodontic appliance, such as changes in bacterial concentration, salivary buffering capacity, salivary acidity (pH) and salivary flow rate. Xylitol stimulates salivary flow and helps restore saliva acid/base balance because it cannot be converted to acid by oral bacteria. To identify the difference in salivary pH before and after chewing xylitol gum in the users of fixed orthodontic appliance. This research is quasi-experimental with one group pretest-posttest design. Samples were students of SMA Kolombo Sleman who used a fixed orthodontic appliance. Data were analyzed using a Wilcoxon test. The salivary pH of the users of a fixed orthodontic appliance before chewing xylitol gum mostly belonged to acid criterion (43.8%), and the base criterion (34.3%). After chewing xylitol gum, the salivary pH of the users of fixed orthodontic appliance mostly belonged to a neutral criterion (78.1%). The results of the Wilcoxon test showed that the salivary pH before and after chewing gum xylitol in the users of fixed orthodontic appliance had a P value of 0.027 <? 0.05. There is a significant difference in salivary pH before and after chewing xylitol gum in users of fixed orthodontic appliance.